American Foulbrood in the Czech Republic: ERIC II Genotype of Paenibacillus Larvae Is Prevalent - Biová, Jana; Bzdil, Jaroslav; Dostálková, Silvie; Petřivalský, Marek; Brus, Jan; Carra, Elena; Danihlík, Jiří (Frontiers in Veterinary Science, 2021)
American foulbrood (AFB) is a dangerous disease of honey bees (Apis mellifera) caused by the spore-forming bacterium Paenibacillus larvae. According to ERIC (Enterobacterial Repetitive Intergenic Consensus) classification, five genotypes are distinguished, i.e. I, II, III, IV and V, which differ in their virulence and prevalence in colonies. In the Czech Republic, AFB prevalence is monitored by the State Veterinary Administration; however, the occurrence of specific P. larvae genotypes within the country remain unknown. In this study our aim was to genotype field P. larvae strains collected in the Czech Republic according to the ERIC classification. In total, 102 field isolates from colonies with AFB clinical symptoms were collected from various locations in the Czech Republic and the PCR genotypization was performed using ERIC primers. We confirmed the presence of both ERIC I and II genotypes, while ERIC III, IV and V were not detected. The majority of samples (n=82, 80.4%) were identified as ERIC II, while the ERIC I genotype was confirmed only in 20 samples (19.6%). In contrast to other European countries, the ERIC II genotype is predominant in Czech honey bee colonies. The ERIC I genotype was mostly detected in border regions close to Poland, Slovakia and Austria.